2008
DOI: 10.1074/jbc.m709707200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of WRN Protein Cellular Localization and Enzymatic Activities by SIRT1-mediated Deacetylation

Abstract: Werner syndrome is an autosomal recessive disorder associated with premature aging and cancer predisposition caused by mutations of the WRN gene. WRN is a member of the RecQ DNA helicase family with functions in maintaining genome stability. Sir2, an NAD-dependent histone deacetylase, has been proven to extend life span in yeast and Caenorhabditis elegans. Mammalian Sir2 (SIRT1) has also been found to regulate premature cellular senescence induced by the tumor suppressors PML and p53. SIRT1 plays an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 40 publications
8
126
2
1
Order By: Relevance
“…For example, it is possible that deacetylation of RECQL4 by the as-yet-unidentified deacetylase regulates its acetylation status. Indeed, Li et al recently reported that deacetylation of WRN helicase by the SIRT1 deacetylase regulates WRN-mediated cellular responses to DNA damage (Li et al, 2008). Additional experiments are planned in our laboratory to determine the possible effects of deacetylation of RECQL4 on its cellular localization and other roles in DNA metabolism.…”
Section: Journal Of Cell Science 122 (8)mentioning
confidence: 99%
“…For example, it is possible that deacetylation of RECQL4 by the as-yet-unidentified deacetylase regulates its acetylation status. Indeed, Li et al recently reported that deacetylation of WRN helicase by the SIRT1 deacetylase regulates WRN-mediated cellular responses to DNA damage (Li et al, 2008). Additional experiments are planned in our laboratory to determine the possible effects of deacetylation of RECQL4 on its cellular localization and other roles in DNA metabolism.…”
Section: Journal Of Cell Science 122 (8)mentioning
confidence: 99%
“…SIRT1 regulates these pathways through deacetylating Ku70, [59][60][61] Nijmegen breakage syndrome protein (NBS1), 25 apurinic/apyrimidinic endonuclease-1 (APE1), 62 xeroderma pigmentosum group A/C (XPA/XPC), 63,64 and Werner syndrome protein. 65 As a result, inhibition of SIRT1 can sensitize cancer cells to several types of DNA damageinducing agents. 46,66,67 …”
Section: Sirt1 Enhances Dna Damage Repair In Cancer Cellsmentioning
confidence: 99%
“…First, acetylation of H3K56, a substrate for SIRT1, is increased in multiple cancers (12). Second, SIRT1 has been reported to play a key role in repairing DNA-breaks and maintaining genome stability (13,14). Moreover, SIRT1 has been shown to suppress the growth of colon cancer by inhibiting E2F1 or b-catenin (15,16).…”
Section: Introductionmentioning
confidence: 99%